Pengaruh Penerapan Prinsip-Prinsip Good Governance terhadap Kualitas Pelayanan Publik di Samsat Banyumas - Nurhaeni, Ismi Dwi Astuti; Zulaechah, Zain Afdha (Universitas Sebelas Maret, 2023)
The phenomenon of public services in the government bureaucracy in Indonesia is still very rife with problems, many brokers are found, service procedures that still seem convoluted, time and price uncertainties cause services to be reasonably difficult to reach by the community, one of which is the case in public services. in Samsat Banyumas, where there are still a lot of brokers who charge high prices for making documents. This is certainly contrary to the principles of Good Governance. So it is important to examine how much influence the application of the principles of Good Governance has in the Samsat Banyumas. This study uses the theory of Good Governance by UNDP (United Nations Development Programme), namely participation, rule of law, transparency, responsiveness, consensus orientation, equity, effectiveness and efficiency, accountability, strategic vision, and service quality theory by Zeithaml, Parasuraman, and L. Berry, namely measuring service quality with five dimensions of service quality (physical evidence, reliability, responsiveness, assurance, and empathy). The research method used is descriptive quantitative with data collection techniques, namely questionnaires distributed via Google form. Data analysis in this study used simple regression analysis and partial significance test and the coefficient of determination. This analysis will explain how strong the influence of the application of the principles of Good Governance is on the quality of public services in Banyumas Samsat. The results of this study indicate that the application of the principles of good governance has a positive effect on the quality of public services, with a significance value of 0.000 <0.05 and a t-count value of 14.034 ≥ t-table 1.9855, which means that variable X has a significant positive effect on variables Y.